Women's 'Retrieval' from Pakistan: 'India's Daughters' and the Emotional History of Partition. Issue 4 (4th July 2021) - Dandekar, Deepra
Abstract: The Partition of 1947 remains an important reference point for Hindu nationalist political discourse in India, defining its relationship with Pakistan and Muslims in South Asia. This article investigates the use of the label 'India's daughters' by the BJP-led NDA government (2014–15), a term originally used to describe Hindu and Sikh women retrieved from Pakistan in 1947. It offers an example of the emotional power wielded by Partition metaphors and demonstrates the BJP's attempts to insert itself into the emotional history of Partition by transforming the meanings of its terms. The case of Uzma Ahmad's retrieval from Pakistan acts as a case in point, illustrating the BJP's increasing attempts to harness Partition semantics.